Filling the gap between Earth observation and policy making in the Black Sea catchment with enviroGRIDS. Issue 46 (February 2015) - Lehmann, A.; Giuliani, G.; Mancosu, E.; Abbaspour, K.C.; Sözen, S.; Gorgan, D.; Beel, A.; Ray, N.
Highlights: Gap analysis on Earth Observation systems to serve the needs of two international commissions. Preparation of openly available tutorials on "Bringing GEOSS services into practice". Black Sea Catchment Observation System registered into GEOSS. First spatially explicit scenarios of climatic, demographic and land use changes, and hydrological modelling of the entire Black Sea catchment. Pilot studies in other Societal Benefit Areas such as biodiversity, ecosystem, agriculture, energy, and risk assessments. Abstract: The environmental status of the Black Sea is obviously closely related to its catchment. Being a closed sea, this large water body drains an area of more than 2 million km 2, encompassing 23 countries inhabited by more than 180 million people. The main environmental issues faced by the Black Sea catchment are the same as elsewhere in Europe. These problems are exacerbated by global changes with drastic changes predicted in temperature and precipitation by the end of the century, as well as land use and demographic changes. These environmental problems are taking place in a complex geopolitical situation. In this particular context, data sharing is essential to inform managers and policy-makers about the state of the environment, which will ultimately influence the state of the Black Sea itself. The enviroGRIDS project was set up in order to promote international data sharing initiatives such as the Global Earth Observation System of Systems and the European INSPIRE directive. The enviroGRIDS project was successful in reaching the following objectives: (a) performing a gap analysis on existing Earth observations systems in the region; (b) developing regional capacities at institutional, infrastructure and human resource levels; (c) creating regional scenarios to set the scene for plausible climatic, demographic and land use futures; (d) building the first hydrological model for the entire Black Sea catchment; (e) developing the Black Sea Catchment Observation System based on interoperability standards and Grid computing technologies; (f) showcasing data sharing in several case studies, addressing important environmental issues while building a network of people with improved capacity on data sharing principles. These relative successes should not, however, hide the difficulties in making the necessary Earth observation data available to scientists, decision makers and the public, as the mind-sets at all levels are changing slowly. Controlling the access to data is still perceived by many as a necessity to guarantee the power of the state on society and as a way to preserve its security. The need to develop national spatial data infrastructures (SDI) is very important to convince all ministries and data owner that publically funded data should be made publically available. The progress in the implementation of SDI seems more limited by political agendas than by technology. It is clear, however, that implementation of the INSPIRE directive in Europe is a prerequisite for the success of many other environmental policies (e.g. Water Framework Directive; Marine Strategy Framework Directive; Biodiversity strategy 2020).